TA’ARUF DAN KHITBAH SEBELUM PERKAWINAN - Isnadul Hamdi (Institut Agama Islam Negeri Batusangkar, 2017)
This research was motivated by the number of potential married couples who do not perform Ta'aruf (islamic acquintance) process in accordance with Islamic teachings. In addition, there are still parents who tend to make economic and customary factors rather than religious ones. In the practice of khitbah, there are still customary rules that complicate that in turn prevent the marriage. The purpose of this research is to investigate information from the Qur'an about the concepts of Ta'aruf and Khitbah in accordance with Islamic teachings. This research was a library research which was done by collecting, reading, and reviewing books that have something to do with this discussion. The primary sources were the Qur'an and Tafsir related to the concept of Ta'aruf and Khitbah . The results of research showed that the concept of Ta'aruf in Al-Qur'an refers to being familiar with personality, social background, culture, education , family, and/or religion, while khitbah in Al-Qur'an refers to something which is done after the couple have felt they match through ta'aruf process. Khitbah (engagement) can be delivered with indirect or with a clear direct expression. Indirect engagement is done to the widow who is still in the iddah period. While the proposal with a direct expression is dcelivered to the widow who expired the period of iddah and to the virgin. Ta'aruf and khitbah in the Qur'an advocate to prioritize the religious aspect than any other factor since it is only religion that will be able to perpetuate marriage. In contrast, wealth, heredity, position and beauty will fade and one day will be lost. The Qur'anic rules on Ta'aruf and the Khitbah do not allow khalwat (solitary).